Analisis Pembelajaran Berbasis Project Based Learning dalam Meningkatkan Kreativitas Peserta Didik - Budiono, Slamet; Setyariza, Nur Ayu; Kusumawardani, Intan; Widayati, Sri Erna; Handayani, Yekti (TSAQOFAH, 2024)
Project-based learning research (Project Based Learning) is an innovative learning model that focuses on students solving a problem by producing a product, making decisions, carrying out investigative activities so that students' creativity and motivation increases. This learning model trains and develops the ability to solve problems that are oriented towards authentic problems from students' actual lives, to stimulate high-level thinking abilities. Conditions that must be maintained are a conducive, open, negotiated, democratic atmosphere, a comfortable and enjoyable atmosphere so that students can think optimally.